A term mining approach of interview case study on enterprise lean production. (19th September 2017) - Jing, Shuwei; Ho, Zih-Ping; Niu, Zhanwen
Abstract : Lean production improves the capacity of enterprise management innovation (EMI). When enterprises implement lean production, companies need internal and external incentives to drive this forward. In order to make internal and external incentives cooperate, promote the successful implementation of lean production, and improve the capacity of EMI, analysing the driving factors of lean production for internal and external incentives is important. This study adapted enterprise case study method, focused on interviews of different levels of enterprise personnel, and tried to find the key driving factors for internal and external incentives in lean production. In this study, a term mining approach was used to analyse interview texts. After the interview of case study, the experiments proceeded on the basis of the proposed model and approaches. Then interview case texts were analysed by text-mining techniques; this study found important clues in enterprise lean production, which were described as follows: (1) Enterprises should improve their ability in management innovation via completing their objectives of lean production, both in internal and external environments; (2) when an enterprise completes lean operations, the enterprise needs some internal and external incentives to drive their actions; and (3) motivators for different levels of enterprise personnel, such as senior managers, middle managers, junior managers, and basic production personnel and lean experts, were different. The enterprise should operate the different roles in each level of personnel for each enterprise management and innovation mission.